MODEL-MODEL PENGURUSAN ISLAM: SUATU SOROTAN LITERATUR: Islamic Management Models: A Literature Review - Mohammed Fareed, Fatin Rabia’tul Adawiyah (Jurnal Syariah, 2023)
Islamic management is a comprehensive management designed for Islamic-based organizations. There are several models of Islamic management that have been formulated by Muslim experts to describe the concept of Islamic management. Nevertheless, no previous studies have been done to analyze the similarities and differences between the models. Hence, this study aims to describe nine Islamic management models and also to analyze the similarities and differences between them. This is a conceptual study that uses a qualitative method by referring to relevant library sources. The findings are then analyzed by using content analysis. The findings of the study show that there are six identified similarities, namely the aspect of Islamic management philosophy, its goals, the nature of human events, resources, its principles and the involvement of external parties. There are two differences have been identified which are related to the aspect of Islamic management principles and approach. In addition, this study also identifies a model that is considered to be the best Islamic management model.